2015
DOI: 10.1111/jipb.12296
|View full text |Cite
|
Sign up to set email alerts
|

Selective silencing of 2Cys and type‐IIB Peroxiredoxins discloses their roles in cell redox state and stress signaling

Abstract: Peroxiredoxins (Prx) catalyse the reduction of hydrogen peroxide (H2O2) and, in association with catalases and other peroxidases, may participate in signal transduction by regulating intercellular H2O2 concentration that in turn can control gene transcription and cell signaling. Using virus-induced-gene-silencing (VIGS), 2-Cys Peroxiredoxin (2CysPrx) family and type-II Peroxiredoxin B (PrxIIB) gene were silenced in Nicotiana benthamiana, to study the impact that the loss of function of each Prx would have in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Peroxiredoxins (Prxs) are a family of non-haem peroxidases that are widely present in animals, plants and microorganisms. The biological function of these peroxidases is to regulate the balance of ROS and intracellular signal transduction through hydrogen peroxide (H 2 O 2 ), alkyl hydroperoxides, and peroxynitrite [16][17][18][19]. In plants, based on the number and position of conserved Cys residues, Prxs are grouped into four classes: 1CysPrx, 2CysPrx, type-II Prx and PrxQ.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxiredoxins (Prxs) are a family of non-haem peroxidases that are widely present in animals, plants and microorganisms. The biological function of these peroxidases is to regulate the balance of ROS and intracellular signal transduction through hydrogen peroxide (H 2 O 2 ), alkyl hydroperoxides, and peroxynitrite [16][17][18][19]. In plants, based on the number and position of conserved Cys residues, Prxs are grouped into four classes: 1CysPrx, 2CysPrx, type-II Prx and PrxQ.…”
Section: Introductionmentioning
confidence: 99%
“…CLPB1 is an HSP that accumulates rapidly under heat stress and has a vital regulatory effect on plant growth 35 . PrxIIB is usually found in the cytoplasm 35 and has several functions in tobacco, including regulating ascorbate regeneration, maintaining the xanthophyll cycle, and influencing H 2 O 2 production in peroxisomes 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the functions of the chloroplast 2-CPs have been intensively studied ( Baier and Dietz, 1999 ; Broin et al , 2002 ; Awad et al , 2015 ), the precise roles of these redox proteins in heat stress responses have not been fully characterized, particularly in relation to the regulation of autophagy and other antioxidants. Using a similar VIGS approach in Nicotiana benthamiana , a recent study showed that the loss of 2-Cys peroxiredoxin family and type-II peroxiredoxin B proteins impaired the heat stress response through effects on AsA regeneration, the xanthophyll cycle, and downstream abscisic acid signalling ( Vidigal et al , 2015 ). The relationships between the 2-CPs and the ascorbate-mediated detoxification systems are particularly interesting because the chloroplast-localized 2-CPs and the tAPX have overlapping functions in H 2 O 2 removal ( Awad et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%